2017
DOI: 10.5755/j01.ms.23.2.14953
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Parylene Coating for Planar Electroporation Copper Electrodes

Abstract: This paper is focused on the feasibility study of parylene as a biocompatible coating for planar electroporation microelectrodes. The planar parallel and the circular interdigitated electrodes are applied in the analysis. The electrodes feature 100 μm width with a 300 μm gap between anode and cathode. The parylene coating thickness was varied in the 250 nm-2 μm range. The resultant electric field distribution evaluation has been performed using the finite element method. The electrodes have been applied in ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The planar electrode structures proved to be advantageous for this type electroporation experiments (Geng et al 2013;Novickij, Tabašnikov, et al 2017), but various issues, such as the spatial non-uniformity of the electric field distribution, complexity of electrode fabrication, biological compatibility issues, and the voltage breakdown occurrence between the electrodes has to be solved (Novickij, Tabašnikov, et al 2017). Due to this, the variety of available planar electrodes for electroporation is currently limited due to the complexity, price and the electrodes fabrication challenges.…”
Section: Planar Electrodes For Electroporationmentioning
confidence: 99%
“…The planar electrode structures proved to be advantageous for this type electroporation experiments (Geng et al 2013;Novickij, Tabašnikov, et al 2017), but various issues, such as the spatial non-uniformity of the electric field distribution, complexity of electrode fabrication, biological compatibility issues, and the voltage breakdown occurrence between the electrodes has to be solved (Novickij, Tabašnikov, et al 2017). Due to this, the variety of available planar electrodes for electroporation is currently limited due to the complexity, price and the electrodes fabrication challenges.…”
Section: Planar Electrodes For Electroporationmentioning
confidence: 99%
“…However, further studies have reported that square-wave pulses are more efficient during the application of high intensity (tens to hundreds of kV/cm) nanosecond PEFs, due to its enhanced control of the pulse energy [33]. This is an important aspect for the rapidly growing microfluidics-based electroporation technique [34], wherein planar electrode structures have proved to be advantageous [34,35].…”
Section: Of 10mentioning
confidence: 99%
“…The planar electrode structures proved to be advantageous for this type electroporation experiments (Geng & Lu, 2013;Novickij et al, 2017), but various issues, such as the spatial non-uniformity of the electric field distribution, complexity of electrode fabrication, biological compatibility issues, and the voltage breakdown occurrence between the electrodes has to be solved (Novickij et al, 2017). Due to this, the variety of available planar electrodes for electroporation is currently limited due to the complexity, price and the electrodes fabrication challenges.…”
Section: Electronics and Electrical Engineering Elektronika Ir Elektrmentioning
confidence: 99%